3D-Piezoelectric Vibration Energy Harvesters: Design Analyses and Performance Evaluation - Zaman, Izzuddin; Manshoor, Bukhari; Mohamed Salleh, Muhammad; Sambu, Mathan; A. Abuhatira, Ahmed; Saravanabava, Sethupathi (Journal of Advanced Mechanical Engineering Applications, 2026)
Piezoelectric materials (PZT) possess the capability to generate electrical energy through deformation, making them ideal for energy harvesting system that transform vibrational energy into electrical power. This study explores the relationship between the design of PZT beams, their natural frequency, vibration response, and generated voltage using a three-dimensional (3D) finite element model. Three types of cantilever designs were considered, that is, L-beam, T-beam and I-beam with PZT-5A patches attached. Each design was subjected to modal analysis, harmonic response as well as voltage analysis performed through Ansys Workbench. The result of modal analysis shows that I-beam exhibits the highest fundamental natural frequency compared to T-beam and L-beam. The evaluation of vibration response at sinusoidal loading was then performed by conducting harmonic response analysis between 0 to 1500 Hz excitation range. It was found that the L-beam demonstrated the highest displacement amplitude at resonance as compared to the other designs. The amplified deformation was converted into voltage output that was verified by the coupled electromechanical analysis, where the L-beam produced the highest voltage output of 7 V at 35 Hz, which is 89% higher than the T-beam and 439% higher than I-beam. In conclusion, this study demonstrates that beam geometry is one of the keys contributing to the efficiency of piezoelectric vibration energy harvesting systems. By optimizing beam design, we do not merely record vibrations, but we can harvest power to the maximum.